Effect of Bronchodilator and Steroid Use on Heart Disease and Stroke Risks in a Bronchiectasis–Chronic Obstructive Pulmonary Disease Overlap Cohort: A Propensity Score Matching Study - Yeh, Jun-Jun; Yang, Yu-Cih; Hsu, Chung Y.; Kao, Chia-Hung (Frontiers in Pharmacology, 2019)
Background: To determine the effects of bronchodilator, steroid, and anti-arrhythmia drug use on the risk of heart disease/stroke (HDS) in patients with bronchiectasis–chronic obstructive pulmonary disease overlap syndrome (BCOS). Methods: We retrospectively enrolled patients with BCOS (BCOS cohort, n = 1493) and patients without bronchiectasis and chronic obstructive pulmonary disease (COPD) (non-BCOS cohort, n = 5972). The cumulative incidence of HDS was analyzed through Cox proportional regression. We calculated adjusted hazard ratios (aHRs) and their 95% confidence intervals (CIs) for HDS after adjustments for sex, age, comorbidities, long-acting β2-agonist or long-acting muscarinic antagonist (LABAs/LAMAs) use, short-acting β2-agonist or short-acting muscarinic antagonist (SABAs/SAMAs) use, oral steroid (OSs) or inhaled corticosteroid steroid (ICSs) use, and anti-arrhythmia drugs use. Results: The aHR (95% CI) for HDS was 1.08 (0.28–4.06) for patients using LAMAs compared with those not using drugs. Regarding drug use days, the aHRs (95% CIs) were 32.2 (1.79–773.0), 1.85 (1.01–3.39), and 31.1 (3.25–297.80) for those with recent SABAs use, past ICSs use, and past anti-arrythmia drugs use, respectively. Regarding cumulative drug dose, the aHRs (95% CIs) were 2.12 (1.46–3.10), 3.48 (1.13–10.6), 3.19 (2.04–4.99), 28.1 (1.42–555.7), 2.09 (1.32–3.29), 2.28 (1.53–3.40), and 1.93 (1.36–2.74) for those with a low dose of SABAs, medium dose of SABAs, low dose of SAMAs, low dose of ICSs, medium dose of ICSs, low dose of OSs, and medium dose of OSs, respectively. Conclusion: Compared with patients without bronchiectasis and COPD, BCOS patients with recent SABAs, past ICSs, and past anti-arrhythmia drugs use; a low or medium SABAs ICSs, and OSs dose; and a low SAMAs dose had a higher risk of HDS. LAMAs were not associated with HDS.